Pemodelan Kasus Demam Berdarah Dengue di Jawa Barat Menggunakan Regresi Gaussian, Poisson, dan Compound Poisson Tweedie - Sundari, Marta; Sativa, Oryza (Neolectura, 2024)
Dengue Hemorrhagic Fever (DHF) is an infectious disease that remains a serious public health problem in Indonesia, particularly in West Java Province. This study aims to model the number of DHF cases using Gaussian, Poisson, and Compound Poisson Tweedie regression methods based on 2023 data sourced from the West Java Central Statistics Agency (BPS) and the West Java Provincial Health Office. Predictor variables used include humidity, rainfall, real per capita expenditure, poverty ratio, population density, percentage of households with clean and healthy lifestyles, ratio of health facilities, and average altitude of the area above sea level. The analysis results indicate that Gaussian and Poisson regression are less suitable for use because they are unable to handle overdispersion in the data. The Compound Poisson Tweedie model provides the best performance with the smallest Akaike Information Criterion (AIC) value. Three variables that significantly influence the number of DHF cases in West Java in 2023 are rainfall, real expenditure per capitaand the ratio of health facilities, so that the resulting model equation is (2.233 plus 0.001387 times rainfall plus 0.000022 times real per capita expenditure minus 0.015250 times health facility ratio), indicating that rainfall and expenditure increase DHF cases, while more health facilities reduce them.